KARAKTERISASI MORFOLOGI DAN UJI ANTIFUNGI ISOLAT JAMUR Trichoderma spp. DARI TANAH GAMBUT TERHADAP PATOGEN PADA JARAK KEPYAR (Ricinus communis L.) - Aini, Nur; Martina, Atria (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Castor oil (Ricinus communis L.) is an oil producing commodities that plays a role in meeting industrial and economic needs. Infection with the pathogen fungi caused a decrease in the production of castor oil. Biological control using Trichoderma spp. has been widely used. Trichoderma spp. known as one of the benefical biofungicide because it has high antagonistic properties inhibiting the growth pathogenic fungi. The purpose of this study was to obtain isolates and characters as well antifungal test for Trichoderma spp. isolated from peat soil to control pathogen Aspergillus sp. on castor been (Ricinus communis L.). Trichoderma spp. isolated from peat soil in Meranti Islands, Riau. The antagonistic activity the isolates against pathogen Aspergillus sp. was studied in vitro using dual culture and in vivo assay. In this study, six isolates of Trichoderma spp have isolated. Trichoderma sp. GBA5 has the highest growth rate on PDA and TSM medium. Trichoderma sp. GBA3 and Trichoderma sp. GBA4 were most effective in percentage inhibition of mycelial growth of test pathogen i.e 84,55% and 83,71% respectively. In in vivo assay, only Trichoderma sp. GBA5 inhibited pathogen with the percent infected castor capsule was 51.66%.